«Уявлення особистості» як психологічне поняття - Лінь, Цяо (Studies in Comparative Education, 2014)
У статті проаналізовано психологічні аспекти категорії «уявлення особистості». В історичній послідовності розглянуто та систематизовано основні психологічні теорії і концепції вивчення категорії «уявлення». Встановлено, що визначенням психологічного змісту поняття «уявлення» широке коло вчених опікується вже понад тисячу років. Серед відомих учених, увагу яких було спрямовано на розв’язання цієї проблеми, – Р. Ассанджолі, В. Вундт, Т. Рібо, Л. Виготський, С. Рубінштейн, А. Петровський, В. Роменець, Ю. Трофімов та ін. З’ясовано, що загалом дослідники розуміють під уявою – вміння подумки на базі досвіду та власних знань створювати нові об’єкти, ідеї, літературні та музичні твори. В статье проанализированы психологические аспекты категории «представление личности». В исторической последовательности рассмотрены и систематизированы основные психологические теории и концепции изучения категории «представление». Установлено, что уже более тысячи лет широкий круг учених-психологов занимается изученим категории «представление». Среди известных ученых, внимание которых было направлено на изучение данной проблемы, Р. Ассанджоли, В. Вундт, Т. Рибо, Л. Выготский, С. Рубинштейн, А. Петровський, В. Роменець, Ю. Трофимов и др. Исследователи трактуют воображение как умение мысленно на базе опыта и собственных знаний создавать новые объекты, идеи, литературные и музыкальные произведения. This paper analyzes the psychological aspects of the category «personality perceptions». The basic psychological theories and concepts of the study of the category «perception» are considered and systematized in historical sequence. It is established that for more than thousands of years a wide range of scientists have been dealing with defining the psychological contents of the phenomenon «perception». Among the famous scientists whose attention was focused on solving this problem are R. Assandzholi, W. Wundt, T. Ribot, L. Vygotskyi, S. Rubinshteyn, A. Petrovskyi, V. Romenets, Yu. Trofimov etc. It is determined that in everyday life the word «perception» is used in different senses. It may mean understanding, memories, image of a nonexistent object, phenomenon. In scientific psychology the concept of «perception» is considered as a coincidence of any images and their components in time and space (L. Kar); phenomenon capable to create something new from already known (T. Ribot); a complex function able to act simultaneously at several levels: at the level of sensation, feeling, thinking and intuition (R. Assandzholi); reincarnation of the imagery, visual contents of any problem with the aim of its successful solution (L. Vyhotskyi, S. Rubinshteyn); reflection of reality in new unexpected combinations and relations (A. Petrovskyy); a necessary component for predicting the future (L. B. Ermolaieva – Tomina); reflection in the human psyche of the objects and phenomena perceived ever before (M. Variy); creation of images of the objects and processes that have never been perceived and which may not exist in the environment (Yu. Trofimov). The scientists have analyzed the connection of the perceptions with the memory, thinking and understanding, the perception functions have been distinguished, the ways of their development and implementation have been identified. It is established that in various activities the perceptions obtain peculiar features that’s why they are divided into artistic, scientific and technical.